2014
DOI: 10.1371/journal.pone.0092981
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tracheostomy in Critically Ill Patients: A Meta-Analysis

Abstract: ObjectiveTo compare important outcomes between early tracheostomy (ET) and late tracheostomy (LT) or prolonged intubation (PI) for critically ill patients receiving long-term ventilation during their treatment.MethodWe performed computerized searches for relevant articles on PubMed, EMBASE, and the Cochrane register of controlled trials (up to July 2013). We contacted international experts and manufacturers. We included in the study randomized controlled trials (RCTs) that compared ET (performed within 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 30 publications
4
77
1
12
Order By: Relevance
“…In our study majority of the patients (54.76%) underwent tracheostomy within 7 to 10 days of mechanical ventilation which was similar to the studies done by Chaari et al and Huang et al 12,13 In our study, the total incidence of VAP was 44%. In our study out of the 42 patients who had undergone tracheostomy 13 (30.95%) patients had ventilator associated pneumonia which was similar to the study done by Chaari et al 12 Among the non tracheostomised patients 31 (53.44%) out of 58 patients developed ventilator associated pneumonia.…”
Section: Discussionsupporting
confidence: 90%
“…In our study majority of the patients (54.76%) underwent tracheostomy within 7 to 10 days of mechanical ventilation which was similar to the studies done by Chaari et al and Huang et al 12,13 In our study, the total incidence of VAP was 44%. In our study out of the 42 patients who had undergone tracheostomy 13 (30.95%) patients had ventilator associated pneumonia which was similar to the study done by Chaari et al 12 Among the non tracheostomised patients 31 (53.44%) out of 58 patients developed ventilator associated pneumonia.…”
Section: Discussionsupporting
confidence: 90%
“…A recent meta-analysis published for Huang et al evaluated 9 randomized clinical trials with 2,072 patients [12]. Compared to LT or prolonged MV, they did not find significantly difference of ET in terms of short-term mortality [relative risk (RR) = 0.91; 95% confidence intervals (cIs) = 0.81−1.03; P = 0.14] or long-term mortality VAP or duration of MV.…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis of nine randomized clinical trials with 2,072 participants showed that early tracheostomy had no significant influence on clinical outcomes (shortterm mortality, long-term mortality, length of ICU stay, ventilator-associated pneumonia or duration of mechanical ventilation) compared to late tracheostomy or prolonged intubation (42). Although, two more recent analyses suggest superiority of early tracheostomy (43,44), the timing of tracheostomy is dependent mostly on individual and institutional practice.…”
Section: Timing Of Tracheostomymentioning
confidence: 99%